2020
DOI: 10.1016/j.heliyon.2020.e05601
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of diverse organic residues and their long-term effects on available nutrients in a tropical sandy soil

Abstract: Intensive use of sandy soils for agriculture leads to significant land degradation. The application of locally available organic residues can improve soil fertility, particularly in the context of organic farming practices. This research examined nutrient concentrations in locally available organic residues with different biochemical compositions/qualities and investigated the effects of long-term application of these residues on available nutrients, such as P, K, Ca, Mg, Fe, Mn, and Zn, as well as on total or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our results showed that the use of wheat residues positively improved soil P ava , K ava and TN. This result is consistent with the results reported by Sukitprapanon et al [37]. The highest amount of P ava is related to the second incubation month, which is probably due to the decrease in MBP in the second incubation month and the increase in phosphorus mineralization in the soil (Fig.…”
Section: Microbial Strains Enriched Wheat Residues Effects On Soil Or...supporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the use of wheat residues positively improved soil P ava , K ava and TN. This result is consistent with the results reported by Sukitprapanon et al [37]. The highest amount of P ava is related to the second incubation month, which is probably due to the decrease in MBP in the second incubation month and the increase in phosphorus mineralization in the soil (Fig.…”
Section: Microbial Strains Enriched Wheat Residues Effects On Soil Or...supporting
confidence: 93%
“…This result shows that despite the salinity, due to the adaptation of microorganisms to the stress, microbiological activity in the mineralization process of nitrogen still occurs over time, thus promoting the mineralization of nitrogen [38]. The use of organic residues has environmental benefits, such as accumulation of soil organic carbon and reduction of greenhouse gases and availability of plant nutrients in soil [37].…”
Section: Microbial Strains Enriched Wheat Residues Effects On Soil Or...mentioning
confidence: 99%
“…In general, the sandy soil area in Tra On district has a less acidic than that in Vung Liem district. Sandy soils are usually strongly acidic with pH KCl in the range 4.5-5.5 (Sukitprapanon et al, 2020). According to Giang et al (2021) The suitable pH KCl for the growth and development of terrestrial crops is in the range from 5.5 to 6.5.…”
Section: Chemical Characteristics Of Sandy Soil In the Study Areamentioning
confidence: 99%
“…This also applies to garden wastes that, in certain areas, such as the subtropical coast of Andalusia (S Spain), can be used for nutrient supplementation. Among other factors, the waste quality depends on the C:N and lignin:N ratios [6,16,17], the P and K contents [18,19], and the lignin proportion [20]. As shown in previous studies [21], nutrient release can alter soil microbial activity.…”
Section: Introductionmentioning
confidence: 96%
“…Studies concerning Na, Ca, and Mg dynamics in soils after the spreading of crop wastes report correlations among these nutrients and with soil quality [6]. Nevertheless, data on the inputs of micronutrients (Fe, Mn, Cu, and Zn) are widely unavailable.…”
Section: Introductionmentioning
confidence: 99%